Unusual presentation of choriocarcinoma - Balagopal, PG (BioMed Central, 2003)
BACKGROUND: Choriocarcinoma is an aggressive neoplasm arising in the body of the uterus. The disease normally spreads to lung and brain. CASE REPORT: A case of malignant trophoblastic disease with brain metastasis, raised intra cranial pressure and small bowel metastasis presenting with acute abdomen is reported. CONCLUSIONS: Malignant transformation in a hydatidiform mole is rare event. Involvement of gastrointestinal tract is rarer even in presence of disseminated disease. Surgery is the treatment of choice for gastrointestinal complications.